Wacana Kepemimpinan Perempuan Dalam Film â€˜Opera Jawaâ€™ Karya Garin Nugroho - Toni, Ahmad (Fakultas Dakwah IAIN Purwokerto, 2019)
The paper discusses the film by Garin Nugroho based on a discourse analysis developed by Fairclough. The film titled â€œJavanese Operaâ€ directed by Garin became one of the films that raised the theme of Javanese women in domestic and political space. How Garin in the discourse of Javanese women became interesting because his works were widely recognized as coloring the development of national films and his works were recognized internationally. The research method used a qualitative approach, while the analysis used was Faircloughâ€™s discourse analysis. The gender leadership discourse in Indonesia is represented by Garin Nugroho as a dynamic discourse relating to the sociopolitical context and power based on the national philosophy, culture and values of pluralism adopted by the Indonesian people. The socio-political context in this film is how womenâ€™s perspectives are represented as social agents and political agents in looking at the leadership leadership in Indonesia. In the social dimension, Javanese women are represented as the center of male spiritual power which has a strategic role in shaping male leadership character. In the political dimension, Javanese women are represented as agents of public space in the political contestation of power which is realized by various strategic steps in conducting global political competition.